Self-improvement in Victims of Sexual Harassment on Social Media - Nuraida, Tia; Saut H. Hutahaean, Erik; Fahrudin, Adi (Rifa'Institute, 2023)
Introduction: Sexual harassment is any action carried out with unilateral consent, the impact of which can cause psychological changes to the victims. Sexual harassment is often directed at women. One of the psychological effects for victims of sexual harassment is self-blame (self-blame), and continuous self-blame can hinder an individual's ability to take steps forward and develop oneself to achieve self-improvement (self-improvement). Objective: This study analyzes Self-Improvement in Victims of Sexual Harassment on Social-Media. Method: The Scale of Readiness for Self-improvement (SRSI) is the measuring tool used. The number of research participants was 115 respondents to female victims of sexual harassment on social media. Data analysis was performed using simple correlation and regression analysis. Result and Discussion: The results show that self-improvement for victims of sexual harassment on social media is highly categorized. Conclusion: There is a negative relationship between self-improvement and self-blame